2014
DOI: 10.1073/pnas.1403319111
|View full text |Cite
|
Sign up to set email alerts
|

Local genomic adaptation of coral reef-associated microbiomes to gradients of natural variability and anthropogenic stressors

Abstract: Significance Microbial communities associated with coral reefs influence the health and sustenance of keystone benthic organisms (e.g., coral holobionts). The present study investigated the community structure and metabolic potential of microbes inhabiting coral reefs located across an extensive area in the central Pacific. We found that the taxa present correlated strongly with the percent coverage of corals and algae, while community metabolic potential correlated best with geographic location. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
235
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 192 publications
(256 citation statements)
references
References 40 publications
17
235
3
1
Order By: Relevance
“…[54] also estimated the composition of natural reef-associated microbial communities and found that uninhabited reefs associated with a higher per cent cover of reef-building calcifiers were characterized by higher abundances of cyanobacteria [54]. In this study, we found no evidence linking the relative abundance of cyanobacterial sequences obtained from publically available microbial metagenomes to the NCEAS human impact score (methods described in Knowles et al [62]).…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…[54] also estimated the composition of natural reef-associated microbial communities and found that uninhabited reefs associated with a higher per cent cover of reef-building calcifiers were characterized by higher abundances of cyanobacteria [54]. In this study, we found no evidence linking the relative abundance of cyanobacterial sequences obtained from publically available microbial metagenomes to the NCEAS human impact score (methods described in Knowles et al [62]).…”
Section: Discussioncontrasting
confidence: 60%
“…There is a clear relationship between changing numbers and biomass of water-column microbes and the makeup of the benthos (e.g. microbialization); however, microbes in the water column are very different in terms of types and metabolic potential than those on the benthic surface [7,53,54]. The work presented here takes a more in depth look at microbes in the water column on coral reefs experiencing different levels of microbialization.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a similarly sized dataset on reef-associated microbes, the best parameter explained only 15% of taxonomic variation and 18% of metabolic variation (Kelly et al, 2014). Variations in water column microbial communities appear easier to predict.…”
Section: Resultsmentioning
confidence: 98%
“…Coral-associated microbial community is highly dynamic, with seasonal fluctuations (Kimes, Johnson, Torralba, Nelson et al, 2013), but can suffer significant phase shifts throughout environmental stress gradients (Dinsdale, Pantos, Smriga, Edwards et al, 2008;Kelly, Williams, Barott, Carlson et al, 2014), and with eutrophication (Kline, Kuntz, Breitbart, Knowlton et al, 2006), bleaching and disease (Sekar, Kaczmarsky, & Richardson, 2008;Mao-Jones, Ritchie, Jones, & Ellner, 2010;Mouchka, Hewson, & Harvell, 2010), and sea surface warming trends (Tracy, Koren, Douglas, Weil et al, 2015). A significant interaction between macroalgal and turf proliferation, and microbial impacts to Caribbean corals corals Orbicella annularis (Barott, Rodrí guez-Mueller, Youle, Marhaver, 2012) and Porites astreoides (Vega-Thurber, Burkepile, Correa, Thurber et al, 2012) was also documented.…”
Section: Cascading Effects Of Urban Runoff and Eutrophication In A CLmentioning
confidence: 99%